Deflected Nasal Septum (DNS)- Types and Clinical Manifestations - M.Musharaf Baig,Ifra Saeed,Aysha Yousaf (Journal of Rawalpindi Medical College, 2015)
Background: To study the types of DNS and its different types, using Mladina classification as reference. Methods: In this descriptive study patients who presented with nasal symptoms of nasal septal deformity were included. The exclusion criteria included patients with acute nasal infection, patients with other nasal pathologies such as nasal polypi, benign or malignant nasal growths etc and patients with history of previous septal surgery. Symptoms, age, gender, history of previous nasal surgery and query regarding the etiology of the nasal symptoms were recorded. Nasal problem especially nasal obstruction, unilateral or bilateral; nasal discharge, sneezing, sense of smell, headache and epistaxis etc, were recorded. Assessment of nasal septum was done by anterior rhinoscopic examination. Posterior rhinoscopy and nasal endoscopy were performed where required, especially in posterior deflections. A complete nasal examination of every patient was done by inspection and palpation of external nose, anterior rhinoscopy, posterior rhinoscopy; assessment of nasal patency (by fogging on cold spatula and cotton wick methods) and sense of smell,first without and then after topical spray of vasoconstrictive agent (xynosine nasal spray). In patients, with posterior deflections, nasal endoscopy was done, after preparation, to ascertain the type and site of DNS according to Mladina classification. Results: The frequency of DNS was 67% in males and 58% in females. Most of the patients presented between 2nd and 4th decades. Incidence of different types( Type-1 to Type 7) of DNS was 10%,23%,9%,7%,29%,6%,16% respectively. The main complaints of the patients were nasal obstruction (82%), headache (45%), hyposmia (32%), epistaxis (10%), etc. Conclusion: Deflected nasal septum is widely prevalent. The anterior deflections are more common than the posterior deflections. Type-2 and 5 are the commonest types, according to Mladina classification. Nasal obstruction and headache are the common complaints. Nasal endoscopy is important for the diagnosis, especially of posterior deflections.